Characterization of ticks infecting dogs in a hospital population in North Paraná, Brazil - Oyafuso, Mônica Kanashiro (2002)
Many tick-borne disease can infect dogs and human beings. The distribution of the infectious agents transmitted by ticks parallels the geographic distribution of the vectors. Accordingly, we attempted to characterize ticks in dogs from a hospital population in North Paraná State, South Brazil, and to verify the frequency of each tick species in this population. We selected seventy one dogs presented to the Veterinary Hospital of the Universidade Estadual de Londrina with severe tick infestation. Animals with more than 25 ticks were included regardless of the chief complaint or presenting clinical signs. Ten ticks were collected from various parts of the body in each dog. All ticks were toxonomically classified. Four percent of the ticks removed were identified as Amblyomma cajennense, whereas 96% were Rhipicephalus sanguineus. The distribution of ticks was similar to the one observed in urban areas in South and South-east Brazil and compatible from a predominantly urban dog population.